GeoFactory-Coworking: a biblioteca como espaço de interação - Santana, Anderson (Zenodo (CERN European Organization for Nuclear Research), 2023)
This work presents the experience report of the library of the Institute of Geosciences at Universidade de São Paulo in the retrofit of its spaces for the creation of a 24-hour coworking area. The use of this environment and its impact on the visitors flow of the library were analyzed. As a result, a high flow of use of coworking rooms was verified, which resulted in a 59.3% increase in the flow of visitors to the Library in a comparison between 2019 and 2022. This corroborates the need to readjust the library to a new audience that demands much more space than printedcollections.